Correlation of mRNA Expression and Signal Variability in Chronic Intracortical Electrodes - Falcone, Jessica D.; Carroll, Sheridan L.; Saxena, Tarun; Mandavia, Dev; Clark, Alexus; Yarabarla, Varun; Bellamkonda, Ravi V. (Frontiers in Bioengineering and Biotechnology, 2018)
Objective. The goal for this research was to identify molecular mechanisms that explain animal-to-animal variability in chronic intracortical recordings. Approach. Microwire electrodes were implanted into Sprague Dawley rats at an acute (1 week) and a chronic (14 weeks) timepoint. Weekly recordings were conducted, and action potentials were evoked in the barrel cortex by deflecting the rat’s whiskers. At 1 and 14 weeks, tissue was collected, and mRNA was extracted. mRNA expression was compared between 1 and 14 weeks using a high throughput multiplexed qRT-PCR. Pearson correlation coefficients were calculated between mRNA expression and signal-to-noise ratios at 14 weeks. Main Results. At 14 weeks, a positive correlation between SNR and NeuN and GFAP mRNA expression was observed, indicating a relationship between recording strength and neuronal health, as well as reactive astrocyte activity. The inflammatory state around the electrode interface was evaluated using M1-like and M2-like markers. Expression for both M1-like and M2-like mRNA markers remained steady from 1 to 14 weeks. Anti-inflammatory markers, CD206 and CD163 however, demonstrated a significant positive correlation with SNR quality at 14 weeks. VE-cadherin, a marker for adherens junctions, and PDGFR-β, a marker for pericytes, both partial representatives of blood brain barrier health, had a positive correlation with SNR at 14 weeks. Endothelial adhesion markers revealed a significant increase in expression at 14 weeks, while CD45, a pan-leukocyte marker, significantly decreased at 14 weeks. No significant correlation was found for either the endothelial adhesion or pan-leukocyte markers. Significance. A positive correlation between anti-inflammatory and BBB health mRNA markers with electrophysiological efficacy of implanted intracortical electrodes has been demonstrated. This data reveals potential mechanisms for further evaluation to determine potential target mechanisms to improve consistency of intracortical electrodes recordings and reducing animal-to-animal/implant-to-implant variability.